Mortality trends from respiratory system disease and pneumonia in Spain between 1992 and 2001 - Gea-Izquierdo Enrique (Journal of the Selva Andina Research Society, 2018)
Pneumonia is a public health concern and one of the biggest causes of global mortality. The study of time series shows epidemiological information of pneumonia mortality. The objective of this study is to determine respiratory system disease and pneumonia mortality trends in Spain and Andalusia, in the period 1992-2001. According to the average age at death, mortality trend in Spain is bullish and, even until 1999, for the number of deaths for mortality in relation to the respiratory system disease and the age-adjusted rate (European population x 100000 inhabitants). Regarding the number of deaths and age-adjusted rate, pneumonia mortality in Spain and Andalusia remains approximately stable. Average age at death values, in respiratory system disease and pneumonia mortality in Spain, are very close; as well as those related to pneumonia mortality rates in Spain and Andalusia, which are almost identical, so the latter does not differ at national level. Epidemiological surveillance is an essential tool to reduce the burden of mortality pneumonia, and a framework for planning interventions in health promotion. It’s estimated that mortality indicators corresponding to pneumonia and respiratory system disease will improve the results.